IN VIVO STUDY EVALUATES EFFECTIVENESS OF ADDING CIPROFLOXACIN TO CALCIUM HYDROXIDE VERSUS SAUSSUREA COSTUS TO CALCIUM HYDROXIDE MEDICATION AGAINST BACTERIAL BIOFILM IN ROOT CANAL TREATMENT - AL Muhalel, Amal Abdu Al Kareem; Al-Shamahy, Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2024)
Background and objectives: Elimination of root canal bacteria is a perquisite for a successful root canal treatment. This research aims to determine the effectiveness of adding ciprofloxacin versus Saussurea costus extract to calcium hydroxide medicament against bacterial biofilm in root canal treatment in vivo study. Materials and methods: In vivo study on 70 single-rooted human teeth at Sana'a University dental clinics used Saussurea costus extract preparation, including washing, drying, crushing, mixing, centrifugation, drying, and homogenization.The intracanal drug concentration was standardized by mixing 1 g of calcium hydroxide powder with 1 ml of ciprofloxacin or 1 ml of Saussurea costus extract in both groups. Three bacteriological samples were taken before root canal treatment, before Medicaments were placed, and 7 days after, and CFU and bacterial isolation were performed using standard methods. Results: An intragroup analysis showed that all drug groups had a significant decrease in the number of intracanal bacterial cells from S1 to S2 and from S2 to S3 (p<0.0001). When comparing quantitative S1 or S2 data, there was no significant difference between the groups; however, at Sample 3, the Saussurea costus extract calcium hydroxide (34.05±21.8) had considerably higher bacterial counts than the calcium hydroxide + Ciprofloxacin group (11.9±29 CFU). The most isolated bacteria in S1 and S2 were Staphylococcus aureus (58.6%, 51.4%), followed by Klebsiella species (27.1%, 18.6%), Escherichia coli (25.7%, 17.1%), Enterococcus faecalis (22.9%, 15.7%) and Pseudomonas aeruginosa (21.4%, 12.9%). Conclusions: The addition of Ciprofloxacin to calcium hydroxide and Saussurea costus- calcium hydroxide provided further antibacterial effectiveness when used as an intracanal medicament in vivo during root canal treatment. Peer Review History: Received 27 March 2024; Revised 5 May 2024; Accepted 28 June; Available online 15 July 2024 Academic Editor: Essam Mohamed Eissa , Beni-Suef University, Egypt, dressamceutics@yahoo.com Reviewers: Dr. Kingsley C Anukam, University of Benin, Nigeria, kanukam@gmail.com Dr. Liliya Logoyda, Horbachevsky Ternopil State Medical University, Ukraine, logojda@tdmu.edu.ua